Formation of Kiss1R/GPER Heterocomplexes Negatively Regulates Kiss1R-mediated Signalling through Limiting Receptor Cell Surface Expression. Issue 7 (2nd April 2021) - Ke, Ran; Lok, Samson Ian Sam; Singh, Kailash; Chow, Billy Kwok Chong; Janovjak, Harald; Lee, Leo Tsz On
Graphical abstract: Highlights: Screening between Kiss1R and other hypothalamic GPCRs suggested an interaction with GPER. Co-expression of GPER significantly suppresses the Kiss1R-mediated signalling. The reduction of Kiss1R signalling is due to the limited cell surface expression. This mechanism fine-tunes GPCR signaling by limiting the exposure of the receptor to the ligands. Abstract: Kisspeptin receptor (Kiss1R) is an important receptor that plays central regulatory roles in reproduction by regulating hormone release in the hypothalamus. We hypothesize that the formation of heterocomplexes between Kiss1R and other hypothalamus G protein-coupled receptors (GPCRs) affects their cellular signaling. Through screening of potential interactions between Kiss1R and hypothalamus GPCRs, we identified G protein-coupled estrogen receptor (GPER) as one interaction partner of Kiss1R. Based on the recognised function of kisspeptin and estrogen in regulating the reproductive system, we investigated the Kiss1R/GPER heterocomplex in more detail and revealed that complex formation significantly reduced Kiss1R-mediated signaling. GPER did not directly antagonize Kiss1R conformational changes upon ligand binding, but it rather reduced the cell surface expression of Kiss1R. These results therefore demonstrate a regulatory mechanism of hypothalamic hormone receptors via receptor cooperation in the reproductive system and modulation of receptor sensitivity.